PRIVATE SCHOOLS TEACHERS’ SATISFACTION: A CASE STUDY OF DISTRICT DIR LOWER TEHSIL TALASH KPK PAKISTAN - Muhammad Ismail; Qamruz Zaman; Danish Wasim; Neelam; Syed Habib Shah; Shumaila Wazir; Gul KaramKhan; Abdur Rehman (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examined the impact of variables such as Salary, job stability, and Workload on teachers' job satisfaction in the Private School of Tehsil Talash, District, Dir Lower, KPK, Pakistan. A representative sample was selected from the population using Cluster Random Sampling for analysis. Utilizing a logistic regression model, the study identified significant factors influencing teacher satisfaction. The results highlighted the importance of salary, job security, and workload in determining teachers' satisfaction levels. Recommendations include enhancing job security measures for educators, reducing workloads, and hiring well-trained teaching staff to improve teacher satisfaction and ultimately enhance the quality of education.